Rapid Synthesis of Carbon‐Supported Ru‐RuO₂ Heterostructures for Efficient Electrochemical Water Splitting - Dingjie Pan; Bingzhe Yu; John Tressel; Sarah Yu; Pranav Saravanan; Naya Sangoram; Andrea Ornelas‐Perez; Frank Bridges; Shaowei Chen (Advanced Science)
Abstract Development of high‐performance electrocatalysts for water splitting is crucial for a sustainable hydrogen economy. In this study, rapid heating of ruthenium(III) acetylacetonate by magnetic induction heating (MIH) leads to the one‐step production of Ru‐RuO₂/C nanocomposites composed of closely integrated Ru and RuO₂ nanoparticles. The formation of Mott‐Schottky heterojunctions significantly enhances charge transfer across the Ru‐RuO2 interface leading to remarkable electrocatalytic activities toward both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in 1 m KOH. Among the series, the sample prepares at 300 A for 10 s exhibits the best performance, with an overpotential of only −31 mV for HER and +240 mV for OER to reach the current density of 10 mA cm⁻2. Additionally, the catalyst demonstrates excellent durability, with minimal impacts of electrolyte salinity. With the sample as the bifunctional catalysts for overall water splitting, an ultralow cell voltage of 1.43 V is needed to reach 10 mA cm⁻2, 160 mV lower than that with a commercial 20% Pt/C and RuO₂/C mixture. These results highlight the significant potential of MIH in the ultrafast synthesis of high‐performance catalysts for electrochemical water splitting and sustainable hydrogen production from seawater.